Teacher empowerment toward professional development and practices: perspectives across borders - Amzat, Ismail Hussein (Springer Singapore, 2017)
This book gathers a range of contributions from researchers and practitioners across borders with an emphasis on theoretical arguments and empirical data concerning teacher empowerment. It propels readers to explore powerful teaching practices that can further advance the profession as a continuing priority in the system when appropriately utilized.